2013
DOI: 10.4103/0019-5154.113947
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the impact of age, skin tags, metabolic syndrome, body mass index, and smoking on homocysteine, endothelin-1, high-sensitive C-reactive protein, and on the heart

Abstract: Background:Skin tags (STs) are small, pedunculated skin-colored or brown papules that occur around any site where skin folds occur. The literature is short of comprehensive and controlled clinical studies aimed to evaluate the atherogenic risk factors in patients with STs.Aim of Work:The aim of this study is to evaluate the impact of age, STs, metabolic syndrome (METs), body mass index (BMI), and smoking on homocysteine (Hcy), endothelin-1 (ET-1), high-sensitive C-reactive protein (Hs-CRP), and on cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“… 21 In addition, the Centers for Disease Control and Prevention and the American Heart Association (suggest that cardiovascular risks of patients can be categorized according to hs-CRP levels: <1 mg/L for relatively low risk, 1.0 to 3.0 mg/L for moderate risk, >3.0 mg/L for high risk. 22 The two indicators are clinically important for evaluating no-reflow in myocardial infarction, but their relevance remains unclear. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 21 In addition, the Centers for Disease Control and Prevention and the American Heart Association (suggest that cardiovascular risks of patients can be categorized according to hs-CRP levels: <1 mg/L for relatively low risk, 1.0 to 3.0 mg/L for moderate risk, >3.0 mg/L for high risk. 22 The two indicators are clinically important for evaluating no-reflow in myocardial infarction, but their relevance remains unclear. 23 …”
Section: Discussionmentioning
confidence: 99%
“…It was reported that even some unexpected dermatological lesions such as skin tags could be related to cardiac diseases. [ 5 ] PPP, which is generally considered an isolated lesion might be also a predictor of some cardiac diseases associated with connective tissue abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies showing associations between skin tags and diabetes mellitus, impaired glucose tolerance, insulin resistance, and disorders of lipid metabolism [8,[10][11][12][13]. In addition, skin tags are one of the independent predictors of the occurrence of cardiac disease [14].…”
Section: Introductionmentioning
confidence: 99%